Capturing the patient experience in systemic lupus erythematosus: Are widely used measures fit-for-purpose and adherent to FDA PRO guidance recommendations? - Kayleigh R. Majercak; Eleanor M. Perfetto; Ester Villalonga-Olives (SpringerOpen, 2022)
Abstract Background The 2009 Food and Drug Administration (FDA) patient-reported outcome (PRO) guidance outlines characteristics of rigorous PRO-measure development. There are a number of widely used PRO measures for Systemic Lupus Erythematosus (SLE), but it is unknown how well the development processes of SLE PRO measures align with FDA guidance; including updated versions. The objective of this study was to assess how well the LupusQoL and LupusPRO, and corresponding updated versions, LupusQoL-US and LupusPROv1.8, align with Food and Drug Administration (FDA) 2009 patient-reported outcome (PRO) guidance. Methods LupusQoL and LupusPRO were selected as the most widely studied and used Lupus PROs in the UK and US. Original (LupusQoL (2007) and LupusQoL-US (2010)) and revised (LupusPROVv1.7 (2012) and LupusPROv1.8 (2018)) versions were reviewed. We used FDA PRO guidance to create evaluation criteria for key components: target population, concepts measured, measurement properties, documentation across the phases of content validity (item-generation and cognitive interviewing, separately) and other psychometric-property testing. Two reviewers abstracted data independently, compared results, and resolved discrepancies. Results For all measures, the target population was unclear as population characteristics (e.g., ethnicity, education, disease severity) varied, and/or were not consistently reported or not considered across the three phases (e.g., LupusQoL item-generation lacked male involvement, LupusPRO cognitive-interviewing population characteristics were not reported). The item-generation phase for both original measures was conducted with concepts elicited via patient-engagement interviews and item derivation from experts. Cognitive interviewing was conducted via patient feedback with limited item-tracking for original measures. In contrast, the revised measures assumed content validity. Other psychometric testing recommendations (reliability, construct validity, ability to detect change) were reported for both original and revised measures, except for ability to detect change for revised measures. Conclusions The SLE PRO measures adhere to some but not all FDA PRO guidance recommendations. Limitations in processes and documentation of the study population, make it unclear for which target population(s) the current Lupus measures are fit-for-purpose.